Exploring the Impact of Individual Factors in Taking Cervical Cancer Screening: A Content Analysis - Vian Haji Rasul; Mohhammad Ali Cheraghi; Zahra Behboodi Moghadam (Iran University of Medical Sciences, 2016)
Background: Cervical cancer remains the leading cause of cancer death among women in developing country. In Iraqi Kurdistan Region, few women undergo screening and the incidence of cervical cancer is on the increase as is the case in most developing countries. The purpose of this study was to explore women's individual factors affecting the performance of the cervical cancer screening in Kurdistan Region, Iraq. Methods: The present study adopted a qualitative design based on conventional content analysis approach. Purposive sampling was used to select 22 women who had either had a Pap-Smear or refused to have one. Semi structured in depth interviews were conducted with each individual to collect data. Data were collected from August 7, 2015 to July 22, 2016. The criteria for including samples for this study were aS follows: 1) Married Kurdish women who are living in Kurdistan Region, Iraq, 2) Willingness to participate in the study, and 3) Not undergone cervical cancer screening. Non Iraqi Kurdish women were excluded. Each interview lasted for 42-70 minutes on average. In order to analyze the collected data, the obtained purified codes were compared and simultaneously clustered and classified under certain themes using their similarities and differences. Results: Seven main themes including age, educational level, having multiple full-pregnancies, existence of signs and symptoms of cervical cancer, psychological factors, poverty, and marital status emerged during the data analysis.  Conclusion: The findings of this study indicated that individual factors can prevent women from cervical cancer screening in Kurdistan Region, Iraq. Understanding these factors may lead to the development of effective programs and policies to improve cervical cancer screening uptake by Kurdish women.